2015
DOI: 10.1139/apnm-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid exerts its antidiabetic effect by modulating insulin-signalling molecules in the liver of high-fat diet and fructose-induced type-2 diabetic adult male rat

Abstract: Ferulic acid (FA) is a phenolic phytochemical known for its antidiabetic property The present study is designed to evaluate the mechanism behind its antidiabetic property in high-fat and fructose-induced type 2 diabetic adult male rats. Animals were divided into 5 groups: (i) control, (ii) diabetic control, (iii) diabetic animals treated with FA (50 mg/(kg body weight · day)(-1), orally) for 30 days, (iv) diabetic animals treated with metformin (50 mg/(kg body weight · day)(-1), orally) for 30 days, and (v) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 57 publications
5
75
0
Order By: Relevance
“…Apocynin has the potential to improve insulin sensitivity 68 . Ferulic acid improved insulin sensitivity and hepatic glycogenesis but inhibits gluconeogenesis to maintain normal glucose homeostasis in type 2 diabetic rat 69 . Also, it has a potential to modulate adipogenesis via expressing of heme oxygenase-1 (HO-1) and suppressing C/EBPα and PPARγ, triglyceride–synthesizing enzymes, fatty acid synthase (FASN) and acetyl-CoA carboxylase (ACC) 70 .…”
Section: Discussionmentioning
confidence: 94%
“…Apocynin has the potential to improve insulin sensitivity 68 . Ferulic acid improved insulin sensitivity and hepatic glycogenesis but inhibits gluconeogenesis to maintain normal glucose homeostasis in type 2 diabetic rat 69 . Also, it has a potential to modulate adipogenesis via expressing of heme oxygenase-1 (HO-1) and suppressing C/EBPα and PPARγ, triglyceride–synthesizing enzymes, fatty acid synthase (FASN) and acetyl-CoA carboxylase (ACC) 70 .…”
Section: Discussionmentioning
confidence: 94%
“…Here, we have shown that SCCAM possess a similar capacity that NCRAE to enhance the glucose uptake on the L6 cells, indicating the value of the mixture of chicoric acid and chlorogenic acid on insulin sensitivity. The presence of Ferulic acid derivatives in NCRAE can be beneficial since trans-Ferulic acid has been reported to exert an antidiabetic effect by modulating insulin signaling pathway in the liver of type 2 diabetic rats (Narasimhan et al, 2015). The delayed improvement in OGTT can be due to the insulin sensitizing action of NCRAE by caffeoyltartaric acid derivatives and the stabilization of glycosuria may be related to the decrease in basal hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The different compounds present within the SR have been reported to display hypoglycemic, anti-inflammatory and antioxidant effects which have been discussed hereunder. Ferulic acid manifests antidiabetic potential by modulating insulin-signaling molecules [59]. Caffeic acid possesses significant antidiabetic activity [60].…”
Section: Discussionmentioning
confidence: 99%